Effects of gaseous atmosphere and antioxidants on the development and cryotolerance of bovine embryos at different periods of in vitro culture - Souza Rocha-Frigoni, Nathalia Alves de [UNESP]; Silva Leao, Beatriz Caetano da [UNESP]; Nogueira, Eriklis; Accorsi, Monica Ferreira [UNESP]; Mingoti, Gisele Zoccal [UNESP] (Cambridge Univ Press, 2015)
This study examined the effects of antioxidant supplementation and O-2 tension on embryo development, cryotolerance and intracellular reactive oxygen species (ROS) levels. The antioxidant supplementation consisted of 0.6 mM cysteine (CYST); 0.6 mM cysteine + 100 mu M cysteamine (C+C); 100 IU catalase (CAT) or 100 mu M beta-mercaptoethanol (beta-ME) for 3 or 7 days of in vitro culture (IVC). Two O-2 tensions (20% O-2 [5% CO2 in air] or 7% O-2, 5% CO2 and 88% N-2 [gaseous mixture]) were examined. After 7 days of antioxidant supplementation, the blastocyst frequencies were adversely affected (P<0.05) by CYST (11.2%) and C+C (1.44%), as well as by low O-2 tension (17.2% and 11.11% for 20% and 7% O-2, respectively) compared with the control (26.6%). The blastocyst re-expansion rates were not affected (P > 0.05) by the treatments (range, 66-100%). After 3 days of antioxidant supplementation, the blastocyst frequencies were not affected (P > 0.05) by any of the antioxidants (range, 43.6-48.5%), but they were reduced by low O-2 tension (P<0.05) (52.1% and 38.4% for 20% and 7% O-2, respectively). The intracellular ROS levels, demonstrated as arbitrary fluorescence units, were not affected (P > 0.05) by antioxidant treatment (range, 0.78 to 0.95) or by O-2 tension (0.86 and 0.88 for 20% and 7% O-2, respectively). The re-expansion rates were not affected (P > 0.05) by any of the treatments (range, 63.6-93.3%). In conclusion, intracellular antioxidant supplementation and low O-2 tension throughout the entire IVC period were deleterious to embryo development. However, antioxidant supplementation up to day 3 of IVC did not affect the blastocyst frequencies or intracellular ROS levels.
Keywords: Antioxidants; Cryotolerance; Embryo culture; Embryo development; Gaseous atmosphere